Iconography associated with Agave L. (Agavaceae) - Giraldo-Cañas, Diego (2023)
Iconography had involved the study, description, classification, and interpretation of an icon by sourcing and correlating textual sources with the evidence of the icon. Studies on Tropical American iconography had remained focused on identifications of ancient drawings, specifically in relation to the plethora of naturalistic expeditions. However, the studies on Agave iconography remain without development. This study was based on premises of iconographic analyses. 18 species were recognized and four morphological styles were identified. Agave americana L. and A. salmiana Otto ex Salm-Dyck were the most common species in the analized iconography. My hope is that this paper will open up new possibilities of research, enjoyment, and understanding in the vast resources of the plant iconography, ancient and recent.